Health Disparities in Patients Seeking Physiological Surgical Treatment for Lymphedema. Issue 1 (20th October 2022) - Shakir, Afaaf; Coalson, Elam; Beederman, Maureen; Froimson, Jill R.; Chang, David W.
Abstract : Background: Previous studies have demonstrated racial disparities in breast cancer treatment and secondary lymphedema. However, no studies have yet examined the effects of race and socioeconomic status on physiological surgical treatment for lymphedema. The authors aimed to evaluate whether disparities exist within patients seeking physiological surgical lymphedema treatment. Methods: A retrospective review was performed of patients presenting for physiological surgical treatment of lymphedema from 2013 to 2019. Data on demographics, medical history, socioeconomic factors, lymphedema, and treatments were collected. Results: A total of 789 patients (712 women and 77 men) seeking physiological surgical treatment of lymphedema were selected. Their mean age was 54.4 ± 13.4 years. A total of 620 patients (78.5%) self-reported as White, 120 (15.2%) as Black, 17 (2.2%) as Asian, five (0.6%) as Hispanic, and eight (2.4%) as multiracial. A total of 566 patients (71.7%) met criteria for surgical candidacy. White race was associated with increased rates of surgical candidacy compared with Black race (46.6% versus 77.2%; P < 0.0001). Compared with White patients, Black patients presented with a longer symptom duration (11.07 versus 6.99 years; P < 0.001), had a higher body mass index (mean, 34.5 versus 28.1; P < 1 × 10 –10 ), had a higher International Society of Lymphology stage ( P < 0.05), and were less likely to have maximized medical treatment for lymphedema (30.8% versus 55.4%; P < 0.01). Conclusions: This study demonstrates racial disparities in patients seeking physiological surgical treatment for lymphedema. Black patients present later with more severe disease, receive less nonsurgical treatment before consultation, and are less likely to meet criteria for physiological surgery. Improved patient and provider education on lymphedema and appropriate diagnosis and nonsurgical treatment is of primary importance to address this disparity.